"Raking-in Technique:" Removal Of Brachiocephalic Vein Thrombus Using AngioVac® Device Within A Stented Venous Segment. (2016) - Erben, Y.; Mena-Hurtado, C.; Bonde, P.
Abstract : Introduction: A case is reported of left brachiocephalic vein thrombus removal using the Angiovac device within a stented venous segment via a through-and-through access technique. Report: This novel technique involves obtaining through-and-through access from the left basilic vein to the right femoral vein, which then facilitates the advancement of the Angiovac device to successfully remove in a stepwise fashion the thrombus present within a stented region of the left brachiocephalic vein. Discussion: The Angiovac device has been shown to be very useful and effective at removing large amounts of thrombus, tumor, and foreign bodies within arterial and venous systems successfully. This novel technique uses the through-and-through venous access approach to allow for this device to remain close to the targeted area of thrombus burden and prevent damage of the already existing stents in this region. Highlights: Novel technique to extract thrombus in a stented segment of vessel. Through-and-through access technique from the left basilica vein to the right femoral vein. Central venous thrombectomy using angioplasty balloon.